Long-acting reversible contraception utilization and associated factors among women in extended postpartum period in Hossana town, southern Ethiopia: cross sectional study - Biruktawit Fekade Woldu; Tadesse Lelago Ermolo; Lidiya Gutema Lemu; Negeso Gebeyehu Gejo (BMC, 2020)
Abstract Background In low and middle-income countries, 95% of postpartum women want to avoid a pregnancy for 2 years, but 70% are not using contraception. Delay in use of contraception by couples during postpartum period can result in many unwanted pregnancies. Long-acting reversible contraception (LARC) is ideal for postpartum women. Therefore this study aimed at assessing the prevalence and factors associated with LARC use among postpartum women. Methods Facility based cross sectional study was conducted from July 23-Aug 25, 2018. Systematic random sampling technique was employed to recruit a total of 381 women in extended postpartum period visiting Child Immunization service in hosanna health institutions. Pretested structured questionnaire was used for data collection. Data was analyzed by SPSS version 20. Binary and multiple logistic regression analysis was done. The presence and strength of association was determined using AOR with its 95% CI. Variables with P value less than 0.05 were considered as statistical significant. Results The prevalence of LARC use was 36.5% (95%CI (33.05-39.95)). The main reason for not using LARC was fear of side effect and false information. Previous use of LARC (AOR = 3.3, 95%CI (1.7-6.5)) and have ever discussed with health providers on LARC (AOR = 2.5, 95%CI (1.1-5.74)) were found to be significantly associated with LARC use. Conclusions The utilization of LARC among postpartum women was found to be higher than other studies in Ethiopia. Provision of effective contraceptive counseling during Antenatal, delivery and postnatal care services with emphasis on LARC/Postpartum Intra-Uterine Device is important.